Gambaran Higiene Perorangan Pedagang Terasi di Pasar Tradicional Kota Kendari Tahun 2023 - Almas Azatil'ismah; Febriana Muchtar; Nurmaladewi Nurmaladewi (KOLONI, 2024)
Terasi is a fermented shrimp paste or fish paste with unique aroma and flavor. Terasi has been used as a seasoning of chili paste (sambal) and other cuisines in Indonesia. However, concerns on the potential risk of disease transmission or foodborne illnesses arise from the lack of personal hygiene practices among sellers of food products, including terasi in wet markets. It is considered imperative to promote proper personal hygiene practices among terasi sellers to maintain the quality and safety of the food products being sold in the markets. This research was performed to analzye the personal hygiene practices among terasi sellers in Kendari City Traditional Market in 2023. This quantitative research employed an observational descriptive method, which data were collected from questionnaires and interviews. The research findings reveal that 32 out of 33 terasi sellers have met the 10 indicators of personal hygiene standards as outlined in Minister of Health Regulation No. 17 of 2020 concerning Healthy Markets, whereas one vendor falls short of meeting the specified personal hygiene criteria.